Zerumbone inhibits interleukin-6 and induces apoptosis and cell cycle arrest in ovarian and cervical cancer cells - Abdelwahab, S.I.; Abdul, A.B.; Zain, Z.N.; Hadi, A.H. (2012)
Interleukin-6 is one of the factors affecting sensitivity to cytotoxic agents. Therefore, the current study was designed to investigate the role of IL-6 and IL6 receptors in the cytotoxic effects of zerumbone in ovarian and cervical cancer cell lines (Caov-3 and HeLa, respectively). Exposure of both cancer cells to zerumbone or cisplatin demonstrated growth inhibition at a dose-dependent manner as determined by the MTT (3-[4,5-dimethylthiazol-2-yl]-2,Sdiphenyltetrazolium bromide) reduction assay. Both laser scanning confocal microscopy and TUNEL assay showed typical apoptotic features in treated cells. The studies conducted seems to suggest that zerumbone induces cell death by stimulating apoptosis better than cisplatin, based on the significantly higher percentage of apoptotic cells in zerumbone's treated cancer cells as compared to cisplatin. In addition, zerumbone and cisplatin arrest cancer cells at G2/M phase as analyzed by flow cytometry. Our results indicated that zerumbone significantly decreased the levels of IL-6 secreted by both cancer cells. In contrast, HeLa and Caov-3 cells were still sensitive to cisplatin and zerumbone, even in the presence of exogenous IL-6. However, membrane-bound IL-6 receptor is still intact after zerumbone treatment as demonstrated using an immune-fluorescence technique. This study concludes that the compound, zerumbone inhibits both cancer cell growth through the induction of apoptosis, arrests cell cycle at G2/M phase and inhibits the secretion levels of IL-6 in both cancer cells. Therefore, zerumbone is a potential candidate as a useful chemotherapeutic agent in treating both cervical and ovarian cancers in future.